Improved neonatal outcome after active management of prolonged pregnancies beyond 41+2 weeks in nulliparous, but not among multiparous women. (1st November 2017) - Lindegren, Lina; Stuart, Andrea; Herbst, Andreas; Källén, Karin
Abstract: Introduction: Prolonged pregnancies are associated with adverse maternal and fetal outcome. In Sweden, no national guidelines exist for when to induce prolonged pregnancies. Material and methods: Singleton cephalic prolonged pregnancies (defined as ≥ 41 +3 gestational weeks) during 2001–2013 ( n = 199 770) were identified using the Swedish Medical Birth Register. The maternity units were divided into three groups (tertiles) based on the proportion of pregnancies ≥ 42 +3 gestational weeks among all pregnancies ≥ 41 +3 weeks. The pregnancy outcome among women delivered at the units with the most expectant management of prolonged pregnancies (> 17.6% proceeding to 42 +3 weeks), was compared with that among women delivered at units with the most active management (< 12.6% proceeding to 42 +3 weeks). Odds ratios (OR) were calculated using simple and multiple logistic regression. Adjustments were made for year of delivery, hospital level, maternal age, body mass index, and smoking. Results: Among primiparas, an increased risk of Apgar score < 7 at 5 minutes [odds ratio (OR) 1.27, 95% CI 1.16–1.41] and meconium aspiration (OR 1.49, 95% CI 1.14–1.95) was found after birth at most expectant units compared with most active units, but among multiparas, no such associations were detected. A decreased rate of cesarean section was found for both primiparas (OR 0.83, 95% CI 0.80–0.86) and multiparas (OR 0.82, 95% CI 0.77–0.86) at units with expectant vs. active management. No association between perinatal death and delivery‐unit specific management of prolonged pregnancies was detected. Conclusions: Offspring to primiparas might gain from a more active management of prolonged pregnancies, whereas no such improvement of neonatal outcome among multiparous women was detected.